High Burden of HBV-Infection and Atypical HBV Strains among HIV-infected Cameroonians - Salpini, Romina; Fokam, Joseph; Ceccarelli, Laura; Santoro, Maria-Mercedes; Nanfack, Aubin; Martin Sosso, Samuel; Kowo, Mathurin; Cento, Valeria; Torimiro, Judith; Sarmati, Loredana; Andreoni, Massimo; Colizzi, Vittorio; et al. (Current HIV Research, 2016)
Aim: To investigate the prevalence and genotypic profile of overt and occult hepatitis-B infection (OBI) among HIV-infected individuals in Cameroon. Methods: 212 HIV-infected Cameroonians, aged 37.6 [IQR: 32.6-46.6] followed-up at the University Health Centre in Yaoundé, were tested for HBsAg, anti-HBs, anti-HBc IgG/IgM, HBV-DNA and anti-HCV IgG. HBV positive cases were tested for Hepatitis Delta virus (HDV) using anti-HDV IgG and HDV-RNA. Liver function was assessed by alanine and aspartate aminotransaminases. OBI was defined as negative-HBsAg and detectable HBV-DNA. In occult or overt HBVinfected participants, HBV reverse transcriptase (RT)/surface (S) sequences were analyzed for drug resistance, immuneescape mutants, and phylogeny. Results: Overall, 78.3% (166/212) participants had past/ongoing HBV-exposure, with 39.1% (83/212) carrying “HBcAbpositive alone”. Prevalence of overt HBV (positive-HBsAg) was 11.8% (25/212), prevalence of HBV and HDV was respectively 6.9% (12/175) and 12% (3/25). Phylogeny of HBV-RT/S revealed the co-circulation of genotypes A and E. All HBV-coinfected participants harbored HBV strains with at least one immune-escape mutation. Of note, one HBV variant carried the vaccine-escape mutation G145R that hinders HBsAg neutralization by antibodies. For the first time, a novel 9 aa-deletion (s115-s123), located in the HBsAg “a” determinant, was found concomitantly with OBI. A stop codon in the S region (associated with increased risk of hepatocellular carcinoma) was found in six cases. Conclusion: High prevalence of overt/occult HBV-infection and circulating atypical strains highlight the importance of HBV-surveillance among HIV-infected Cameroonians and strategies to detect OBI in highly endemic countries.
Keywords: drug resistance